ChemInform Abstract: Synthesis and Investigation of Novel Spiro‐isoxazolines as Anticancer Agents. Issue 31 (August 2015) - Das, Prasanta; Omollo, Ann O.; Sitole, Lungile J.; McClendon, Eric; Valente, Edward J.; Raucher, Drazen; Walker, Leslie R.; Hamme, Ashton T. II
Abstract Several spiro‐isoxazolines are prepared via 1, 3‐dipolar cycloaddition followed by intramolecular cyclization of either alcohol or carboxylic acid precursors.